Digital Policing Models Transform Law Enforcement Practices, Impacting Public Trust and Legitimacy - Asmara, Agung; Mubarok, Jamil; Sianturi, Kurnia Desyanto; Sembiring Meliala, Adrianus Eliasta; Siregar, Roswita Berliana (Jurnal Ilmu Kepolisian, 2026)
This research investigates the impact of digital policing and the transformation of law enforcement practices on public trust and police legitimacy in Indonesia, using the case study of Polda Metro Jaya's Jakarta Smart City Policing program. The study employs a sequential explanatory mixed methods approach, combining quantitative and qualitative data to assess the influence of digital technologies like artificial intelligence, facial recognition, and big data analytics on policing practices. The results show that the transformation of law enforcement practices has a stronger impact on public trust compared to digital policing, with both elements indirectly affecting police legitimacy through public trust. The findings highlight the importance of transparency, accountability, and community engagement in strengthening police legitimacy. The model fit testing, using indices like Goodness of Fit Index (GFI) and Comparative Fit Index (CFI), indicates a reasonable fit, although there is room for improvement in some areas. This study contributes to the literature on digital policing in developing countries and provides practical recommendations for Indonesian police to enhance the relationship between law enforcement and the public.